2021
DOI: 10.1007/s12029-021-00637-7
|View full text |Cite
|
Sign up to set email alerts
|

Significant Response to Camrelizumab Plus Targeted Drugs in Recurrent Intrahepatic Cholangiocarcinoma: a Case Report and Literature Review

Abstract: Purpose Intrahepatic cholangiocarcinoma is the second most common primary liver cancer, and is associated with a poor prognosis and rising incidence rate. Methods Here, we reported the case of a middle-aged Asian male who presented with a 9.5-cm liver lesion and was diagnosed with intrahepatic cholangiocarcinoma. Results The patient experienced recurrence three times, twice following radical resection and standard a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This has resulted, it was found that Camrelizumab can bind highly specifically to the C, C’, and FG ends of the PD-1 molecule, enabling it to exhibit high affinity and occupancy for the PD-1 receptor. This allows Camrelizumab to more effectively block the PD-1/PD-L1 pathway and promote the release of IFNγ by T cells ( 26 ). Camrelizumab exhibits potent anti-tumor activity with an IC50 of 0.7 nmol/L and an EC50 of 0.38 nnmol/L when binding to PD-1.Tislelizumab, another PD-1 inhibitor approved by the CFDA, is widely used in the treatment of common malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted, it was found that Camrelizumab can bind highly specifically to the C, C’, and FG ends of the PD-1 molecule, enabling it to exhibit high affinity and occupancy for the PD-1 receptor. This allows Camrelizumab to more effectively block the PD-1/PD-L1 pathway and promote the release of IFNγ by T cells ( 26 ). Camrelizumab exhibits potent anti-tumor activity with an IC50 of 0.7 nmol/L and an EC50 of 0.38 nnmol/L when binding to PD-1.Tislelizumab, another PD-1 inhibitor approved by the CFDA, is widely used in the treatment of common malignancies.…”
Section: Discussionmentioning
confidence: 99%